Pedagogical Challenges in English for Specific Purposes: Integrating Social Science Perspectives in Albanian Higher Education - Hoxhaj, Ervin; Kaba, Flavia; Biba, Redinela (European Journal of Social Science Education and Research, 2025)
English for Specific Purposes (ESP) has become an essential element in higher education, providing students with language competencies specific to their academic and professional fields. This paper critically examines the pedagogical challenges of ESP implementation in Albanian higher education, addressing how institutional constraints, resource limitations, and social factors influence teaching practices and learning outcomes. Through survey data from dentistry students at the University of Tirana, the study identifies persistent barriers including limited resources, inadequate instructor training, resistance to curriculum changes, and lack of standardization in ESP programs. The findings reveal that effective ESP implementation requires alignment between pedagogical approaches, student needs, and institutional realities. Social and educational dynamics such as resource allocation, faculty preparedness, and institutional support significantly shape ESP effectiveness. The study emphasizes that ESP must be understood not merely as a linguistic concern but as an educational challenge shaped by broader social and institutional contexts. These findings highlight the necessity for context-specific solutions to improve ESP programs and strengthen the connection between curriculum and professional language demands, providing practical insights for enhancing ESP teaching practices in Albanian higher education and informing similar efforts across European contexts.